Formulation of zeolite supported nano-metallic catalyst and applications in textile effluent treatment. Issue 4 (August 2020) - Rashid, Tazien; Iqbal, Danish; Hazafa, Abu; Hussain, Sadiq; Sher, Falak; Sher, Farooq
Graphical abstract: Highlights: The borohydride method was used to synthesize a novel natural zeolite-supported nano-zerovalent iron (NZ-nZVI) catalyst. The unprocessed naturally mined zeolite was used as support for nZVI to decrease the aggregation and cost. The synthetic acid orange 52 dye was removed over 94.86 % after 180 min treatment with novel natural zeolite modified nZVI. More than 60 % of dye removal was observed within the first 10 min of treatment with NZ-nZVI at 15 mg/L concentration. NZ-nZVI/SPC Fenton system also effectively removed the green, magenta, and blended colour from the actual textile effluents. Abstract: Textile industry is one of the major industries worldwide and produces a huge amount of coloured effluents. The presence of coloured compounds (dyes) in water change its aesthetic value and cause serious health and environmental consequences. However, the present investigation was carried out to minimize and reduce the colour compounds discharged by the textile industries through a nano-scaled catalyst. This study is mainly focused on the explanation of nanoparticles aggregation by deposition on natural zeolite, and utilization of this natural zeolite as supported material to nano zerovalent iron (NZ-nZVI) in the form of liquid slurry with sodium percarbonate acting as an oxidant in a Fenton like system for the removal of synthetic CI acid orange 52 (AO52) azo dye, in textile effluent. The nano-scaled zerovalent irons were synthesized by borohydride method in ethanolic medium. UV–vis spectrophotometry, FTIR, EDX, SEM, and XRD (powdered) analysis were used for the investigations of surface morphology, composition, and properties of natural zeolite supported nZVI and study the dye removal mechanism. The XRD spectrum revealed that clinoptilolite is the major component of natural zeolite used, while EDX found that the iron content of NZ-nZVI was about 9.5 %. The introduction of natural zeolite as supporting material in the formation of iron nanoparticle resulted in the partial reduction of aggregation of zerovalent iron nanoparticles. The findings revealed that the 94.86 % removal of CI acid orange 52 dye was obtained after 180 min treatment at 15 mg/L initial dye concentration. The highest rapid dye removal of about 60 % was achieved within the first 10 min of treatment at the same dye concentration. Furthermore, the actual dyeing effluent including green, magenta, and the blended colour was successfully decolourized by natural zeolite-supported nZVI/SPC Fenton process. It is concluded that the acceleration of corrosion of NZ-nZVI, breaking of azo bond, and consumption of Fe 2+ were the possible mechanisms behind the removal of AO52 dye. It is also recommended that NZ-nZVI/SPC Fenton process could be a viable option for effluent and groundwater remediation.